2014
DOI: 10.1002/jsfa.6683
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A released back into the medium by Saccharomyces cerevisiae as a function of the strain, washing medium and fermentative conditions

Abstract: Apart from the removal of OTA, release of the toxin is a variable process and relies upon the strain effect; a significance of the other factors of the design (sugar concentration, temperature) was found only for a single isolate. Thus evaluation of the stability of the complex yeasts/OTA should be an additional trait to select promising functional yeasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
(49 reference statements)
1
13
0
Order By: Relevance
“…As reported previously (Bevilacqua et al, 2014) the amount of the toxin release back into the solution, increased following the treatments. Finally, the amount of the toxin released back to the aqueous, toxin-free solution was used as dependent variable for a two-way ANOVA analysis; temperature, sugar and DAP addition were used as independent factors.…”
Section: Ota-s Cerevisiae Complex Stabilitysupporting
confidence: 53%
See 4 more Smart Citations
“…As reported previously (Bevilacqua et al, 2014) the amount of the toxin release back into the solution, increased following the treatments. Finally, the amount of the toxin released back to the aqueous, toxin-free solution was used as dependent variable for a two-way ANOVA analysis; temperature, sugar and DAP addition were used as independent factors.…”
Section: Ota-s Cerevisiae Complex Stabilitysupporting
confidence: 53%
“…In addition, we found only a slight effect of DAP addition in the last treatment. This effect, as well as the interaction strain  temperature, suggested that the physico-chemical factors of the environment could affect the surface properties of yeast cells and thus the removal and the release of the toxin (Bevilacqua et al, 2014).…”
Section: Strainsmentioning
confidence: 98%
See 3 more Smart Citations